PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA - Guslinda Guslinda; Gustimal Witri (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2018)
This study is based on low learning students’ social science outcomes. The purpose of this study is to improve the learning outcomes of IPS with the application of cooperative learning model type Make A Match. This research method using Action Research, this research conducted two cycles, each cycle of two meetings and a one-time test. This research conducted by 20 students of third-grade elementary school. The result of this research obtained average students’ learning outcomes 73.75 with enough categories and on the second cycle, students’ learning outcomes increased again to 80.50 categorized well. The results of the first cycle, the teacher during the learning process less understanding of the method of cooperative type Make A Match so difficult to apply. But in the second cycle, make A Match cooperative method can be applied maximally. The conclusion of this research was the model of make-Match type cooperative has been successfully applied optimally in the learning result social science class.